Is ADHD a way of conceptualizing long-term emotional stress and social disadvantage? - Erlandsson, Soly I.; Hornborg, Christoffer; Sorbring, Emma; Dauman, Nicolas (Frontiers in Public Health, 2022)
Background: The neuropsychiatric, deficit perspective on children and youth diagnosed with ADHD prohibits a multidimensional approach where socioeconomic status, family stress and relationships are relevant factors to examine. Assessments of ADHD through the use of rating scales and short-term interventions may lead to over diagnosis and to a reductionistic approach. This literature review aims to address research outside the prevailing discourse on ADHD as an organic brain dysfunction and broaden the perspectives on children’s behavioral difficulties and medicalization. Methods: An applied, mixed-method, systematic review was allocated in two profiles: (a) includes 26 peer-reviewed articles, both English and French, with a search focus on ADHD in children and youth related to Attachment styles and relationships; (b) comprehends 14 peer-reviewed articles focusing on ADHD in children and youth related to medicalization. Results: In reported studies, researchers approached correlations between ADHD and attachment in different ways, and in most cases, there was a caution to address causality. Parental style was found to be both buffering and aggravating for the appearance of ADHD. In the French studies, the diagnosis was conceptualized as a relational phenomenon where the child’s behavior was inseparable from family member’s suffering. Interview data revealed that teachers rather than physicians appeared to be the ‘engine’ of the medicalization approach. Overall, media seemed to provide an unobjectionable view of the medicalization of children diagnosed with ADHD. Discussion: Professionals and researchers need to acknowledge that ADHD has a strong connection to economic disadvantage, social status, and familial care. The academic discourse of addressing brain dysfunctions might serve the unintended purpose of masking emotional stress and social disadvantage that manifests across generations. Considering the medicalization of ADHD, a psychosocial approach to ADHD including family, and socioeconomic issues could imply a lesser focus on medication as a first choice. Conclusion: This review article illustrates how children’s difficulties in terms of ADHD symptoms can be addressed through a paradigm where emotional dysregulation is understood through relational factors rather than as a neuropsychiatric disorder.To avoid an overly reductionistic and medicalized approach to children’s behavioral difficulties, it is time to reiterate the value of the biopsychosocial perspective.